Design of a fractional order PID controller using GBMO algorithm for load–frequency control with governor saturation consideration - Zamani, Abbasali; Barakati, S. Masoud; Yousofi-Darmian, Saeed (ISA transactions, 2016)
Load–frequency control is one of the most important issues in power system operation. In this paper, a Fractional Order PID (FOPID) controller based on Gases Brownian Motion Optimization (GBMO) is used in order to mitigate frequency and exchanged power deviation in two-area power system with considering governor saturation limit. In a FOPID controller derivative and integrator parts have non-integer orders which should be determined by designer. FOPID controller has more flexibility than PID controller. The GBMO algorithm is a recently introduced search method that has suitable accuracy and convergence rate. Thus, this paper uses the advantages of FOPID controller as well as GBMO algorithm to solve load–frequency control. However, computational load will higher than conventional controllers due to more complexity of design procedure. Also, a GBMO based fuzzy controller is designed and analyzed in detail. The performance of the proposed controller in time domain and its robustness are verified according to comparison with other controllers like GBMO based fuzzy controller and PI controller that used for load–frequency control system in confronting with model parameters variations. •Governor saturation limit is considered in two-area power system model.•Fractional order PID controller is tuned based on GBMO algorithm.•GBMO based FOPID acts far better than GBMO based fuzzy PD and PI controllers.•The robustness of the system is examined.